A novel multi-CDK inhibitor P1446A-05 restricts melanoma growth and produces synergistic effects in combination with MAPK pathway inhibitors. Issue 7 (2nd July 2016) - Eliades, Philip; Miller, David M.; Miao, Benchun; Kumar, Raj; Taylor, Michael; Buch, Shama; Srinivasa, Sreesha P.; Flaherty, Keith T.; Tsao, Hensin
ABSTRACT: Nearly 100% of melanomas have a defect in the p16 INK4A :cyclin D-CDK4/6:RB pathway, leading to abnormal cell cycle control and unregulated cellular proliferation. Here, we report that P1446A-05, a novel multi-CDK inhibitor has significant inhibitory activity against cutaneous and uveal melanoma. Mechanistic studies revealed that P1446A-05 inhibits phosphorylation targets of CDK members, and induces cell cycle arrest and apoptosis irrespective of melanoma genotype or phenotype. Additionally, we show preclinical evidence that P1446A-05 can synergize with other small molecule inhibitors previously studied in melanoma. Collectively, these data demonstrate that targeting cell cycle and transcriptional CDKs with a small molecule multi-CDK inhibitor is a viable approach for developing novel anti-melanoma therapeutics.